2008
DOI: 10.1007/s00109-008-0397-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal changes characterize head and neck cancer with poor prognosis

Abstract: It is well established that genetic alterations may be associated to prognosis in tumor patients. This study investigates chromosomal changes that predict the clinical outcome of head and neck squamous cell carcinoma (HNSCC) and correlate to characteristic clinicopathological parameters. We applied comparative genomic hybridization (CGH) to tissue samples from 117 HNSCC patients scheduled for radiotherapy. Genomic aberrations occurring in more than five patients were studied for impact on locoregional progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…In addition, miR-204 is located at the cancer-associated genomic region 9q21.1-q22.3 locus in human head and neck cancer [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-204 is located at the cancer-associated genomic region 9q21.1-q22.3 locus in human head and neck cancer [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…FANCA has been previously screened in various cancers for genetic and epigenetic alterations. Moreover, in the array-based analysis of Bauer et al (39) the region 16q23-q24 harboring the FANCA gene showed a significant gain associated with lower survival rates in HNSCC patients. Hypomethylation described in this study may be an alternative mechanism to gene amplification potentially leading to an increased gene activity.…”
Section: Discussionmentioning
confidence: 97%
“…Clustering both DNA strands significantly reduces ability of DNA repair machinery to operate, and repair of cross-link involve a highly complexed networks. At the higher structural rank this cause high chromosomal instability (Bauer et al, 2008).…”
Section: Dna Cross-linkersmentioning
confidence: 99%
“…Some array-based data (Sparano et al, 2006) demonstrates the copy number alterations (CNA) in regions covering FA genes BRCA1, BRCA2, FANCD2, and FANCG but no direct associations with the disease were found. In contrast, FANCA has been analyzed in arrayCGH-based study (Bauer et al, 2008), where the region 16q23-q24 (FANCA locus) showed a significant gain associated with lower survival rates in HNSCC patients.…”
Section: Wwwintechopencommentioning
confidence: 99%